Van den Broek and Bakema: two types of functionalists. Architecture and Planning Education at Technical College of Delft in Post-war Society - van Es, Evelien (International Planning History Society Proceedings, 2016)
Europe was damaged badly during the Second World War. Despite the sheer size of the task ahead, the significant destruction, and shortage of manpower and building materials, the Netherlands took up reconstruction expeditiously. With unprecedented resilience battered cities and villages re-emerged from the rubble. The reconstruction was a large-scale operation in which industrially manufactured mass housing and a new cityscape were pursued. During the reconstruction Van den Broek and Bakema Architects were one of the largest offices with influential designs such as the Lijnbaan Shopping Center, the new heart of the bombed city of Rotterdam. Both architects showed great social commitment. Because of the grand scale of construction output in the first decades after the war, J.H. van den Broek and J.B. Bakema asked themselves what the architect’s role and responsibility were in an increasingly technology-dominated society. As both architects were professors at the Technical College of the Dutch university town Delft, it is not surprising that this question was the main theme in their teaching. That goes for their inaugural speeches as well. Addressed in 1948 and 1964 – marking the start and the completion of post-war reconstruction – they show that the architect’s focus had shifted profoundly.